The Highest Retail Price Checker for Web Based Medical Equipment and Necessities - Muhammad Daffa Nugroho (Bina Nusantara University, 2022)
In the business world that is in medical equipment and staples for customers, the availability and also the need for data is also very important. As time goes on, the data is getting more diverse, which makes various products that are uniform but have significant price differences. This triggers confusion for customers to choose a product, so a price checking application is needed. The purpose of this report is to create a price comparison website application that displays the best prices for medical equipment products and staples. The data collection methodology uses Ideation which collects related journals, books, and credible sources. The application design methodology uses the Waterfall method for web development and maintenance. Product data retrieval is done by using the HTML Web Scraping method. How to test the application is done by Alpha Testing and Beta Testing and also Checking Input Output with BlackBox Testing. From the results of data collection and Web Development PriceCheck provides benefits where customers can find out the best price for the product they are looking for which is also available at the right store.